A Simulation Of Basic Air Conditioning System As Teaching Tool (ABBM): Basic Air Conditioning System As Teaching Tool (ABBM) - Baharudin, Nurhayati; ABDUL RAHMAN, Khairul Anuar; GERIJIH, DEBIE DEVISSER; RAHIM, MOHD BEKRI; Mohd Suhaimi, Mohamad Faiz Asyrawi (Research and Innovation in Technical and Vocational Education and Training, 2021)
The purpose of this study is to design and develop a simulation product of basic air conditioning system for teaching aids purposes complete with basic air conditioning components such as compressor, condenser, metering device and evaporator. This product is developing purposely for the course MPP1013 (Introduction to Refrigeration and Air Conditioning). This subject is taken by the first year student and usually facing difficulty to understand about the air conditioning system. Additional simulation about the basic concept air conditioning system might improve student understanding and increased their interest.  Through this simulation, it can enhance student understanding about the components that are available in the air conditioning system and explain how the air conditioning system work. This product also can assist teachers in transferring information more easily during the teaching and learning process. Researchers have chosen ADDIE Model as a guide in developing the product design of a basic air conditioning system product simulation as a teaching aid. Five experts in Heating, Ventilation and Air Conditioning were selected by the researchers to provide feedback on the product design of the basic system of air conditioning systems as teaching aids. Overall, this basic air conditioning simulation product design as teaching aids is suitable for use during theoretical and practical learning for the course of MPP1013.